2021
DOI: 10.1111/bph.15353
|View full text |Cite
|
Sign up to set email alerts
|

Sex difference in flux of 27‐hydroxycholesterol into the brain

Abstract: Background and Purpose: The cerebrospinal fluid (CSF)/plasma albumin ratio (QAlb) is believed to reflect the integrity of the blood-brain barrier (BBB). Recently, we reported that QAlb is lower in females. This may be important for uptake of neurotoxic 27-hydroxycholesterol (27OH) by the brain in particular because plasma levels of 27OH are higher in males. We studied sex differences in the relation between CSF and plasma levels of 27OH and its major metabolite 7α-hydroxy-3-oxo-4-cholestenoic acid (7HOCA) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…[23] Similarly, a previous study in Sweden in-vestigated the sex differences in 27-OHC metabolism, the results showed that the flux of 27-OHC into the brain is higher in males compared with females. [24] The level of 27-OHC was positively associated with TC, LDL-C, and Non-HDL-C in current study, suggesting that cholesterol metabolism was related to 27-OHC. A community-based cohort study in French recruited nondemented subjects among 65 years and over demonstrated that high TC was correlated to an increase of cognitive decline in men instead of women.…”
Section: Discussionsupporting
confidence: 56%
“…[23] Similarly, a previous study in Sweden in-vestigated the sex differences in 27-OHC metabolism, the results showed that the flux of 27-OHC into the brain is higher in males compared with females. [24] The level of 27-OHC was positively associated with TC, LDL-C, and Non-HDL-C in current study, suggesting that cholesterol metabolism was related to 27-OHC. A community-based cohort study in French recruited nondemented subjects among 65 years and over demonstrated that high TC was correlated to an increase of cognitive decline in men instead of women.…”
Section: Discussionsupporting
confidence: 56%
“…It has been suggested that the deleterious effects of hypercholesterolemia on cognitive dysfunction and neurodegeneration may be mediated by increased flux of 27OH cholesterol across the BBB (Bjorkhem et al, 2009;Loera-Valencia et al, 2019). However, recent studies concluded that circulating 27OH cholesterol does not have a direct effect on BBB permeability, and that an unknown circulatory factor with a level correlated to level of 27OH cholesterol may increase BBB permeability (Parrado-Fernandez et al, 2021). The present study suggests that circulating AT1-AA may be this unknown factor increasing permeability of BBB, as strong correlation between AT1-AA and 27OH cholesterol was observed in our model.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggests that approximately 5 mg of 27-OHC per day flows into the brain and that more 27-OHC will enter the brain if the integrity and function of the BBB is impaired ( Heverin et al, 2005 ; Björkhem et al, 2009 ). Generally, the flux of 27-OHC into the brain is higher in males than females, but oxygen steroid levels are not affected by sex differences ( Parrado-Fernandez et al, 2021 ). In neuronal cells, 27-OHC will be metabolized to 7a-hydroxy-3-oxo-4-cholestenoic acid (7-HOCA) by the action of the CYP7B1 enzyme ( Meaney et al, 2007 ).…”
Section: Cholesterol Homeostasis In the Brainmentioning
confidence: 99%